Landscape Analysis of Financial Flows (LAFF): An inclusive methodology to analyze investment flows in a landscape - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
Based on the successful pilot experiences in Indonesia and Ghana, the LAFF tool was applied to analyse landscapes in the Central Highlands of Vietnam with the goal of identifying investments that would contribute to landscape and community resilience.